Science and technology: a framework for peace - Mariazel Maqueda López; Sheena Kennedy; Solomzi Makohliso; Yves Daccord; Klaus Schönenberger (Communications Engineering)
With global conflicts on the rise, it is crucial for transdisciplinary researchers to become more actively involved in leveraging technology to promote peace. After years of experience and discussions with multiple stakeholders, we have identified specific aspects that require greater attention from science, technology, engineering and mathematics scientists. To address these, we propose a practical framework designed to better integrate professionals from technical disciplines into the field of PeaceTech. This framework is built on four key principles: adopting a common language, prioritizing needs-driven innovation, engaging with diverse stakeholders, and adhering to the do-no-harm principle.